LONG YEARS APICULTURE DATA MODEL OF TURKEY: AN ECONOMETRIC TIME SERIES ANALYSIS - Dogan, Z.; Karagoz, M.; Ozbakir, G. O. (PAKISTAN AGRICULTURAL SCIENTISTS FORUM, 2014)
The empirical studies in the field of apiculture are rare both in Turkey and abroad. Nevertheless the importance of apicultural productions for nutrition and industry is growing. In this study we are modeling long years' apiculture data of Turkey. The employed methodology is a compound of econometric structural modeling combined with time series approach of ARMA. At the first step we have estimated a Cobb-Douglas production function for each of honey and wax production series. Then the residuals are tested for unit roots and searched for ARMA structures. Cobb-Douglas functions of honey and wax productions are significant with relevant ARMA modeling of residuals. We have found that, the elasticities of honey and wax productions against the old type hives are negative while their elasticities against new types are 0.45 and 0.35 respectively. Overall the results are indicative of inelasticity of productions for the number of colonies. This is a clear setback for the productivity of apiculture industry given the high rank Turkey's production and colony numbers in the world ranking. More sophisticated methods should be searched in order to develop productivity and competitiveness of Turkish apiculture in the world markets.
Keywords: Apiculture; Cobb-Douglas Functions; ARMA Modeling; Agriculture; Life Sciences & Biomedicine - Other Topics; Veterinary Sciences